Kelayakan Perangkat Pembelajaran Berorientasi PBI dan Pendidikan Karakter pada Materi Daur Ulang Limbah - HABIBA FATIMAH, RIA (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2012)
Abstract—The research aim is to produce learning tools (syllabus, lesson plans and worksheets) on recycling of waste materials with Problem Based Learning Model Instruction (PBI) and Character Education. Learning tools are developed by 4-D method. The feasibility of learnings tool based validation on lectures. The results was appropriate, the stages of implementation of the RPP can be done well. The application of the learning tools is capable to develop student character so the completeness studying results as well the SKM. Key words: feasibility of learning tools, Problem Based Instruction (PBI), Character Education and Waste Recycling